2020
DOI: 10.1111/mms.12728
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in gut microbial community composition of captive spotted seals (Phoca largha)

Abstract: Age is an important factor that significantly impacts the gut microbiota of various mammals. Captive spotted seals (Phoca largha) provide an ideal opportunity to study how age affects their gut microbiota, excluding other environmental factors, which is a challenge when monitoring wildlife. Here, the bacterial composition of the feces of captive spotted seals from four age groups were analyzed; namely, pup (<1 year old), juvenile (1-2 years old), subadult (2-3 years old), and adult (≥4 years old). Firmicutes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 40 publications
3
20
2
Order By: Relevance
“…We found that gut microbiome alpha-diversity moderately declined with adult age, and that host age predicted 4.3% of the variance in gut microbiome beta-diversity. This is consistent with prior studies conducted in chimpanzees (Pan troglodytes) (108), and spotted seals (Phoca largha) (109), which report a general decline in gut microbiome diversity with host aging, but is not consistent with studies conducted in humans (110), or yaks (Bos grunniens) (111). In spotted hyenas from the Serengeti (112), juveniles have slightly less diverse gut microbiomes than adults, which could be true of the population we studied, but we did not sample juveniles.…”
Section: Gut Microbiomes Are Individualized In Wild Spotted Hyenassupporting
confidence: 93%
“…We found that gut microbiome alpha-diversity moderately declined with adult age, and that host age predicted 4.3% of the variance in gut microbiome beta-diversity. This is consistent with prior studies conducted in chimpanzees (Pan troglodytes) (108), and spotted seals (Phoca largha) (109), which report a general decline in gut microbiome diversity with host aging, but is not consistent with studies conducted in humans (110), or yaks (Bos grunniens) (111). In spotted hyenas from the Serengeti (112), juveniles have slightly less diverse gut microbiomes than adults, which could be true of the population we studied, but we did not sample juveniles.…”
Section: Gut Microbiomes Are Individualized In Wild Spotted Hyenassupporting
confidence: 93%
“…As well as being a common commensal, Escherichia/Shigella are well‐characterized pathogens of humans, and one of the main causes of bacterial diarrhea (Khalil et al, 2018 ) but known to be more common in the young of many mammalian species (Chung et al, 2012 ). This genus is, typically, more prevalent in the microbiota of young mammals or those yet to mature and less abundant in mature mammals with a healthy, stable microbiome (Castaño‐Rodríguez et al, 2018 , Tian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each ASV was assigned to a taxonomy according to the SILVA database (Yilmaz et al ., 2014), and an ASV abundance table was constructed. Singletons (number of tags in a specific ASV = 1) were discarded to improve data analysis efficiency (Tian et al ., 2020) and ASV tables were normalized using a standard number of tags according to the sample with the least tags (45 128 tags) (Zhao et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%